Structure of the influenza virus A H5N1 nucleoprotein: implications for RNA binding, oligomerization, and vaccine design - Ng, Andy Ka-Leung; Zhang, Hongmin; Tan, Kemin; Li, Zongli; Liu, Jin-huan; Chan, Paul Kay-Sheung; Li, Sui-Mui; Chan, Wood-Yee; Au, Shannon Wing-Ngor; Joachimiak, Andrzej; Walz, Thomas; Wang, Jia-Huai; et al. (The FASEB journal, 2008)
The threat of a pandemic outbreak of influenza virus A H5N1 has become a major concern worldwide. The nucleoprotein (NP) of the virus binds the RNA genome and acts as a key adaptor between the virus and the host cell. It, therefore, plays an important structural and functional role and represents an attractive drug target. Here, we report the 3.3-Å crystal structure of H5N1 NP, which is composed of a head domain, a body domain, and a tail loop. Our structure resolves the important linker segments (residues 397-401, 429-437) that connect the tail loop with the remainder of the molecule and a flexible, basic loop (residues 73-91) located in an arginine-rich groove surrounding Arg150. Using surface plasmon resonance, we found the basic loop and arginine-rich groove, but mostly a protruding element containing Arg174 and Arg175, to be important in RNA binding by NP. We also used our crystal structure to build a ring-shaped assembly of nine NP subunits to model the miniribonucleoprotein particle previously visualized by electron microscopy. Our study of H5N1 NP provides insight into the oligomerization interface and the RNA-binding groove, which are attractive drug targets, and it identifies the epitopes that might be used for universal vaccine development.--Ng, A. K.-L., Zhang, H., Tan, K., Li, Z., Liu, J.-h., Chan, P. K.-S., Li, S.-M., Chan, W.-Y., Au, S. W.-N., Joachimiak, A., Walz, T., Wang, J.-H., Shaw, P.-C. Structure of the influenza virus A H5N1 nucleoprotein: implications for RNA binding, oligomerization, and vaccine design.